Traumatic Dental Injury to Primary Teeth (Update Dental College Journal, 2023)
Background: Traumatic dental injuries (TDI) in primary teeth can significantly impact the quality of life of affected children, often leading to discomfort and pain. These injuries encompass various diagnostic categories, such as concussion, luxation injuries, uncomplicated crown fractures, complicated crown fractures, and avulsion.Methods: In April 2023, we conducted an extensive electronic literature search across multiple databases, including Web of Science, Scopus, PubMed, Google Scholar, African Journals Online, ResearchGate, and Google, utilizing the Population, Concept, and Context framework. Search terms and keywords were meticulously combined using Boolean operators. The screening of titles and abstracts of publications related to traumatic dental injuries in primary teeth among children was performed independently by three research assistants. Inclusion criteria encompassed original research articles, case reports, and case series related to traumatic dental injuries in primary teeth among children conducted in African countries. Review articles, systematic reviews, viewpoints, books, letters, editorials, book chapters, perspectives, and news pieces on the subject were excluded.Results: Three independent investigators screened the full texts for inclusion criteria, resulting in the exclusion of twenty-six articles that did not meet the predefined criteria. Six articles were included, as they aligned with the aim of this review. All included studies were cross-sectional in nature.Conclusion: Traumatic dental injuries in primary teeth are a noteworthy concern in children. The key recommendations include prevention strategies, prompt treatment, and continued follow-up within a dental care framework. The studies identified in this review encompassed data from five African countries. Further research involving diverse ethnic populations in Africa is essential to bridge existing knowledge gaps and contribute to the growing body of literature on this topic.Update Dent. Coll. j: 2023; 13(2): 42-44